2021
DOI: 10.3390/toxics9100241
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of PCBs and PBDEs in Fish from a Tropical Lake Chapala, Mexico

Abstract: Lake Chapala is the largest natural freshwater reservoir in Mexico and the third largest lake in Latin America. Lakes are often considered the final deposit of polluting materials; they can be concentrated in the organisms that inhabit them, the water, and the sediments. The PCBs and PBDEs are environmental pollutants highly studied for their known carcinogenic and mutagenic effects. PCB and PBDE bioaccumulation levels were determined in Chirostoma spp., Cyprinus carpio, and Oreochromis aureus. In addition, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 48 publications
(55 reference statements)
0
8
1
Order By: Relevance
“…Te highest and lowest average contents of the 18 monomers analyzed were PCB 169 and PCB 18, with 0.51 ng/g ww and 0.00 ng/g ww, respectively. Te concentration of Σ 18 PCBs in the present study was moderate compared to the concentrations reported in other studies, in Lake Chapala, Mexico (Σ 39 PCBs, 1.06-6.07 ng/g) [24] and Cook County IL, Chicago (11.8-505 ng/g ww) [25].…”
Section: Resultscontrasting
confidence: 90%
“…Te highest and lowest average contents of the 18 monomers analyzed were PCB 169 and PCB 18, with 0.51 ng/g ww and 0.00 ng/g ww, respectively. Te concentration of Σ 18 PCBs in the present study was moderate compared to the concentrations reported in other studies, in Lake Chapala, Mexico (Σ 39 PCBs, 1.06-6.07 ng/g) [24] and Cook County IL, Chicago (11.8-505 ng/g ww) [25].…”
Section: Resultscontrasting
confidence: 90%
“…PCBs bioaccumulate in the adipose tissue of living organisms, so their concentration increases along the trophic web, together with their toxicity for both animals and humans. High-chlorine PCBs have a greater potential for bioaccumulation and biomagnification along the food chain [ 103 , 104 , 105 ].…”
Section: Human Exposure and Bioaccumulation Of Pcbmentioning
confidence: 99%
“…Among all 209 compounds classified as PCBs, 12 (i.e., PCB 77,81,105,114,118,123,126,156,157,167,169 and 189) have physio-chemical and toxicological properties comparable to those of dioxins and furans and are, therefore, called dioxin-like PCBs. Being all coplanar, they can bind to the aryl hydrocarbon receptor (AhR), which is the canonical receptor for 2,3,7,8-tetrachlorodibenzo-p-dioxin [25].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are primarily obtained from industrial activities having different uses, such as flame retardants, coolants, cement, and others. Their presence represents an important contribution to water ecotoxicity (Ecuador, Argentina, Mexico) that affects the integrity of the species that inhabit that ecosystem [53][54][55].…”
Section: Detection Of Contaminants In Watermentioning
confidence: 99%
“…The bioaccumulation of several organic compounds, such as polychlorinated biphenyl compounds (PBCs) and polybrominated diphenyl ethers (PBDEs), in important water bodies, such as Lake Chapala (Mexico), has been reported, through the analysis of samples recollected from water, fish, and sediments from two local seasonal periods. In this case, the fish analyzed were Cyprinus carpio, Oreochromis aureus, and Chirostoma spp., establishing that these chemical substances can reach the lake via industrial activities and strong winds and enter from the Lerma River (Mexico) [55].…”
Section: Detection Of Contaminants In Watermentioning
confidence: 99%